GROUPING PROVINCES IN INDONESIA BASED ON YOUTH DEVELOPMENT INDICATORS IN 2021 - Muhamad Zidan Nuralifian; Rani Nooraeni (ipdn, 2023)
Youth have a vital role in development. Indonesia has an uneven distribution of youth across provinces, with over half concentrated in Java. Many young people are also only sometimes in line with their qualities. Youth development was observed through youth development indicators in 2021. The method used is a multivariate method using cluster analysis. The cluster method applied in this research is hierarchy and partition. Based on internal and stability validity, the hierarchical method for five clusters and the number of clusters is the best. The hierarchical method that has the most significant agglomeration coefficient is complete linkage. There is one province with indicators that are very different from other provinces: Papua as cluster 1. Papua requires massive development in all aspects. Cluster 2 comprises Riau Island, Jakarta, the Special Region of Yogyakarta, Bali, and East Kalimantan. Cluster 3 consists of West Nusa Tenggara, Bengkulu, and Lampung. Cluster 4 consists of West Java, Banten, Central Java, Gorontalo, South Sumatra, and East Java. Meanwhile, cluster 5 consists of the remaining members, with the remaining 19 provinces having the most members. Keywords: Youth Development Indicators, Cluster Analysis, Hierarchy, Partition